Edible bird nest: quality assessment, e-nose gas detection and waste utilization - Sarojini A/P Jeyaraman (School of Bioprocess Engineering, University Malaysia Perlis, 2015)
This study was conducted to determine the purity of EBN, to examine the compositional properties of different grades of EBN samples, to produce useful downstream products from EBN waste and to investigate the ambient air quality of the artificial swiftlet house using the Electronic nose (E-nose) sensor. The samples used were raw unprocessed EBN, different grades (2A, 3A, 4A, 5A and biscuit) of processed EBN samples and waste water from the EBN cleaning process from the swiftlet species Aerodramus fuciphagus from the house EBN. The legitimacy or purity of EBN samples was performed using Fourier Transform Infrared (FTIR) spectroscopy technique. Findings of this study revealed that, the FTIR technique could discriminate the genuine EBN from the adulterated EBN samples. Hence, FTIR technique is a useful tool and rapid technique for the determination of authenticity of EBN and thus as a deterrent to the commercial adulteration of EBN based products.